Factors affecting bank competitiveness during non-economic crises: A study in ASEAN countries - Nga, Phan Thi Hang; Hang, Vo Thi Thu (Tạp chí Nghiên cứu Tài chính - Marketing, 2024)
This investigation examines the essential elements that have shaped the competitive landscape of banks in ASEAN nations during non-economic crises, covering the years from 2010 to 2023. The S.GMM method and necessary tests are used to control regression results. We found empirical evidence that positive influencing factors included: the previous year's competitiveness had an impact of 0,27; the size of banks has an impact of 0,11; the size of equity has an impact at f 1,78; the profitability rate has an impact at 1,22; the growth rate of total assets has an impact of 0,014 on the competitiveness of banks. On the contrary, negative factors include factors such as the ratio of loans to total assets have an impact of -0,049; income diversification has an impact of-2,34; technological innovation or non-economic crisis to competitiveness. The authors also address the interaction between income diversification and technological innovation. Results show that these factors have a negative impact on the dependent variable during the research period. Based on the research results, we propose several implications with the expectation that they will provide useful strategies for enhancing competitiveness in the future, as well as add reliable empirical evidence to upcoming research.